Pengaruh Struktur Kepemilikan Terhadap Corporate Social Responsibility Dan Dampaknya Pada Nilai Perusahaan - Fitriani Nur Latifah; Jacobus Widiatmoko (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study examines the effect of institutional ownership, foreign ownership, and public ownership on CSR with firm size, firm age, and leverage, as control variables on firm value. The research method used is a quantitative method. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2016-2020 with a sample of 90 companies. The analytical method used in this research is multiple linear regression. The results of this study indicate that institutional ownership, foreign ownership, and public ownership have a positive and significant impact on CSR. Testing of the control variables of firm size, firm age and leverage shows that firm size, firm age and leverage have no effect on firm value, while CSR has a direct positive and significant effect on firm value. Keywords : Institutional Ownership, Foreign Ownership, Public Ownership, CSR, Firm Size, Firm Age, Leverage, Firm Value